Geothermal Temperature Slope at the KDD – 1 Well, Kadidia and Surrounding Areas, Nokilalaki, Sigi, Central Sulawesi Province - Irwan Firmansyah; Siswandi Siswandi; Sachrul Iswahyudi; Dudi Hermawan; Santia Ardi Mustofa (Journal of Earth and Marine Technology (JEMT), 2022)
The need for alternative energy other than fossil energy is felt to be increasingly urgent for the fulfillment of domestic electrical energy. In meeting the demand for electricity, the government needs to investigate alternative geothermal energy, to find out the potential for geothermal energy to provide electricity. The realization of this policy is that the government conducts an integrated geothermal investigation to find prospective geothermal areas that can be developed as electric power. Nokilalaki District, Sigi Regency, Central Sulawesi Province is one area that has geothermal potential in Indonesia. The Kadidia geothermal area, Sigi Regency, Central Sulawesi Province is one of the volcanic geothermal fields that have good potential and needs to be investigated further, especially on geological conditions that affect the presence of geothermal energy. The research method used is the method of analyzing the results of field observations. From the observations, it was concluded that the KDD-1 temperature gradient well had a final depth of 703.85 m. The formation temperature is 96.87 ºC at a depth of 700-meters with an average slope value of 12.8 ºC/100 meters, and the estimated temperature at a depth of 1500 m (estimated top reservoir) is 220 ºC.